Partial inhibition of gp130-Jak-Stat3 signaling prevents Wnt-ß-catenin-mediated intestinal tumor growth and regeneration - Phesse, T.; Buchert, M.; Stuart, E.; Flanagan, D.; Faux, M.; Afshar-Sterle, S.; Walker, F.; Zhang, H.; Nowell, C.; Jorissen, R.; Tan, C.; Hirokawa, Y.; et al. (American Association for the Advancement of Science, 2014)
Copyright © 2014 American Association for the Advancement of Science. All Rights Reserved. Most colon cancers arise from somatic mutations in the tumor suppressor gene APC (adenomatous polyposis coli), and these mutations cause constitutive activation of the Wnt-to-ß-catenin pathway in the intestinal epithelium. Because Wnt-ß-catenin signaling is required for homeostasis and regeneration of the adult intestinal epithelium, therapeutic targeting of this pathway is challenging. We found that genetic activation of the cytokine-stimulated pathway mediated by the receptor gp130, the associated Jak (Janus kinase) kinases, and the transcription factor Stat3 (signal transducer and activator of transcription 3) was required for intestinal regeneration in response to irradiation-induced damage in wild-type mice and for tumorigenesis in Apc-mutant mice. Systemic pharmacological or partial genetic inhibition of gp130-Jak-Stat3 signaling suppressed intestinal regeneration, the growth of tumors in Apc-mutant mice, and the growth of colon cancer xenografts. The growth of Apc-mutant tumors depended on gp130-Jak-Stat3 signaling for induction of the polycomb repressor Bmi-1, and the associated repression of genes encoding the cell cycle inhibitors p16 and p21. However, suppression of gp130-Jak-Stat3 signaling did not affect Wnt-ß-catenin signaling or homeostasis in the intestine. Thus, these data not only suggest a molecular mechanism for how the gp130-Jak-Stat3 pathway can promote cancer but also provide a rationale for therapeutic inhibition of Jak in colon cancer.